Pathological ATPergic Signaling in Major Depression and Bipolar Disorder - Illes, Peter; Verkhratsky, Alexei; Tang, Yong (Frontiers in Molecular Neuroscience, 2020)
The mood disorders, major depression (MD) and bipolar disorder (BD), have a high lifetime prevalence in the human population and accordingly generate huge costs for health care. Efficient, rapidly acting, and side-effect-free pharmaceuticals are hitherto not available, and therefore, the identification of new therapeutic targets is an imperative task for (pre)clinical research. Such a target may be the purinergic P2X7 receptor (P2X7R), which is localized in the central nervous system (CNS) at microglial and neuroglial cells mediating neuroinflammation. MD and BD are due to neuroinflammation caused in the first line by the release of the pro-inflammatory cytokine interleukin-1β (IL-1β) from the microglia. IL-1β in turn induces the secretion of corticotropin-releasing hormone (CRH) and in consequence the secretion of adrenocorticotropic hormone (ACTH) and cortisol, which together with a plethora of further cytokines/chemokines lead to mood disorders. A number of biochemical/molecular biological measurements including the use of P2X7R- or IL-1β-deficient mice confirmed this chain of events. More recent studies showed that a decrease in the astrocytic release of ATP in the prefrontal cortex and hippocampus is a major cause of mood disorders. It is an attractive hypothesis that compensatory increases in P2X7Rs in these areas of the brain are the immediate actuators of MD and BD. Hence, blood-brain barrier-permeable P2X7R antagonists may be promising therapeutic tools to improve depressive disorders in humans.